New Perspectives on Microsoft Internet Explorer 5 - Carey, Joan (Course Technology, 2000)
Part of our New Perspectives Series, this text offers a case-oriented, problem-solving approach to learning the capabilities of this powerful browser. This Introductory title covers basic to intermediate features of Microsoft Internet Explorer, from browsing to web page creation